2018
DOI: 10.1055/s-0038-1675815
|View full text |Cite
|
Sign up to set email alerts
|

Giant Cell Tumor of Bone: Review of Current Literature, Evaluation, and Treatment Options

Abstract: Giant cell tumor of bone is a benign albeit aggressive tumor commonly affecting the bones of the knee. Patients with these tumors present with pain, swelling, and inability to bear weight on the involved extremity. These destructive tumors typically arise in the metaphyseal region of the long bones in individuals in the second, third, and fourth generations of life. Histologically, the multinucleated giant cells are the hallmark of the lesion, easily recognized on histological review, which recently have becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(142 citation statements)
references
References 34 publications
2
128
0
12
Order By: Relevance
“…The principal of GCTs treatment should be based on completely removing the tumor, reducing recurrence, and preserving or recovering limb function [3,4,18]. In this study, clinical examination revealed no cases of lung metastasis or local GCT recurrence at the last follow-up.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…The principal of GCTs treatment should be based on completely removing the tumor, reducing recurrence, and preserving or recovering limb function [3,4,18]. In this study, clinical examination revealed no cases of lung metastasis or local GCT recurrence at the last follow-up.…”
Section: Discussionmentioning
confidence: 57%
“…Vascularized bula can repair massive-cavity bone defects and save knee joint Many reconstruction procedures, including sandwich technique, arthroplasty, osteoarticular allograft, allograft arthrodesis, and vascularized or non-vascularized bular autograft with or without arthrodesis have been proposed after wide resection of GCT around the knee [3,4,[25][26][27].…”
Section: Extensive Curettage Can Reduce the Risk Of Recurrencementioning
confidence: 99%
See 2 more Smart Citations
“…Several types of adjuvant therapies, including phenol/alcohol, and cryotherapy, have been performed to maximize tumor kill. Meanwhile, the mechanical adjunct of a high-speed burr is performed to extend the margins of the tumor resection [4].…”
Section: Introductionmentioning
confidence: 99%